Characters that Suffered Due to Shortage in the Characters - Ma Feng (Lingua Cultura, 2010)
In this article, the theories about motif and type will be used for analyzing the very types of characters that suffered because of the shortages. To begin with, the analyzing of the differences and similarities of the shortages of each character will be counted on the inside and outside parts of their sufferings. Then the theories of Nietzsche’s and of some myths will be used for analyzing the further reason of the sufferings. At last, investigating the special value those sufferings have brought for literatures and for TV series. Multi-angle perspective is useful for investigating the unique charms of the shortages of characters as well as for finding out new understandings for the types of sufferings.